Caracterización morfóliga y molecular de Nematodos fitoparasíticos asociados con tomate riñón (Solanum lycopersicum L.): estrategias de control en Meloidogyne sp. - Curay Quispe, Segundo Euclides (2018)
ABSTRACT Root root-knot nematodes belonging to the genus Meloidogyne are widely distributed worldwide and they are considered the most important phytopathogens due to their impact on economic importance crops. In the present study, morphometric variations of populations of Meloidogyne sp. collected in different localities from provinces of Cotopaxi and Tungurahua. Additionally, the effect of different doses (1, 2 and 3%) of essential oils of Nicotiana glauca, Ricinus comunis and Brassica carinata for the control of Meloidogyne spp was evaluated. A negative control (tween) and a positive control (Nakar nematicide 1.5 ml/L) were used. Samplings were made in farms planted with tomato in El Tambo, Cunchibamba, Quillan Loma and Izamba (Province of Tungurahua) and in Patain, Rumipamba, Salache, and Santa Ana (Province of Cotopaxi). The extraction of the nematodes was done by using the Baermann funnel. The morphometric data were subjected to a Principal Components Analysis (PCA) to determine the interpopulation variations. A wide variation of the morphometric variables was observed in the juveniles (J2) of the different populations of Meloidogyne sp. collected in Cotopaxi, mainly regarding the length of the body, width in the middle part, length of the stylet and b, while in the populations collected in Tungurahua the populations showed to be similar between them. The Principal Components Analysis explained up to 80.7% of the variation when considering the first three axes and indicated that the variables tail length, esophagus length and width in the middle part of the body had the highest weights to explain this variation. The mortality rate produced by the essential oils increased with the increase of the dose and time of exposure, with the best results when N. glauca oil was used at doses of 2 and 3%, followed by the oil of B. carinata. Based on the effectiveness of thes two essential oils, they could be incorporated into pest management programs against Meloidogyne population, however, field studies are suggested to validate the results under laboratory conditions. In this study molecular characterization was not made due to lack of equipments and time to standardization of the methodology.